Oral History Interview with Susan Turell by Megan Cherrier - Cherrier, Megan; Turell, Susan (My University, 2009)
This interview is part of an oral history project conducted in honor of the 25th anniversary of the Women's Studies Program at the University of Wisconsin - Eau Claire.